2020
DOI: 10.1002/lsm.23240
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Decreases Hyperalgesia in Complex Regional Pain Syndrome: An Experimental Mouse Model Subjected to Nicotine

Abstract: Background and Objectives: Complex regional pain syndrome (CRPS) is defined as an extreme and chronic pain condition, and photobiomodulation has relevance as a complementary treatment for CRPS. The objective of this study was to verify the effects of photobiomodulation (PBMT) therapy protocols at two wavelengths 660 and 830 nm, associated or not to nicotine in complex regional pain syndrome type I (CRPS-I). Study Design/Materials and Methods: Sixty-four Swiss mice were divided into the following groups: (i) Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…As previously described, CRPS-I has three stages [5]. The study by Rodrigues et al [13] evaluated the effects of PBM 660 and 830 nm on CRPS-I and reported that mechanical hyperalgesia decreased significantly from the fourth day of application in the groups treated with PBM 660 and 830 nm, corroborating with the data of the present study, where the group treated with PBM in the acute phase (G3) obtained reduced values of mechanical hyperalgesia. These findings can be explained by the rapid action of PBM, promoting peripheral and sympathetic nerve blockage and reducing pain [17].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As previously described, CRPS-I has three stages [5]. The study by Rodrigues et al [13] evaluated the effects of PBM 660 and 830 nm on CRPS-I and reported that mechanical hyperalgesia decreased significantly from the fourth day of application in the groups treated with PBM 660 and 830 nm, corroborating with the data of the present study, where the group treated with PBM in the acute phase (G3) obtained reduced values of mechanical hyperalgesia. These findings can be explained by the rapid action of PBM, promoting peripheral and sympathetic nerve blockage and reducing pain [17].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies [13,14,24,26,32,33,39,40] have evaluated the effects of different wavelengths including 660 and 830 nm on CRPS-I, and found a reported decrease in mechanical hyperalgesia [13], decreased temperature, and early functional recovery [33] in the groups treated with PBM Group 1: control (placebo), Group 2: photobiomodulation (PBM) applied to the paw with complex regional pain syndrome type I (CRPS-I) from the warm phase, Group 3: PBM applied to the paw with CRPS-I from the acute phase, Group 4: PBM applied close to the area of the region between L4 and L5 from the warm phase, Group 5: PBM applied close to the area of the region between L4 and L5 from the acute phase, Group 6: PBM applied at two points: right paw and region between L4 and L5 from the warm phase, Group 7: PBM applied at two points: right paw and region between L4 and L5 from the acute phase, 3rd: third evaluation day, 7th: seventh evaluation day, 14th: fourteenth evaluation day, 21st: twenty-first evaluation day. .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations